TEACHING AT THE RIGHT LEVEL'S IMPACT ON ELEMENTARY STUDENTS' ENGLISH SKILLS: A CASE STUDY - Ermawati Ermawati; Azwan Azwan (Al-Irsyad: Journal of Education Science, 2025)
This study aims to analyze the impact of implementing the Teaching at the Right Level (TaRL) method on the development of English language skills of elementary school students at English House Makassar. The research employed a descriptive qualitative method with a case study approach. The subjects consisted of three Beginner 1 Elementary Level students and one instructor. Data were collected through documentation of learning outcomes, classroom observations, and interviews with the teacher. The results indicate that the application of the TaRL method positively impacted the development of students' vocabulary, grammar, speaking, reading, and writing skills. Furthermore, students demonstrated active participation, high enthusiasm, and increased motivation and confidence. The teacher assessed that this method facilitates the learning process as materials and strategies can be tailored to students' actual abilities, although its implementation demands high creativity and faces challenges related to differences in student motivation. This study concludes that TaRL is relevant for application in elementary-level English language learning, particularly due to its ability to create more inclusive, structured, and enjoyable learning. This research recommends that the TaRL method be more widely developed for subjects based on foundational skills, supported by creative learning media appropriate to the students' ability levels.